НЕКОТОРЫЕ ПАРАМЕТРЫ АТЕРОГЕНЕЗА У БОЛЬНЫХ АНЕМИЯМИ - В. Г. Желобов; А. В. Туев; Л. А. Некрутенко (Архивъ внутренней медицины, 2014)
Influence hypoxia on parameters of the metabolic module (lipide a spectrum, lipide peroxidase, antioxidizing activity of blood) and vasodilatum function endothelium is investigated at various pathogenetic variants of an anemia. Development of an anemia, irrespective of conducting mechanism pathogeny and etiology, is accompanied by antiatherogenous changes lipide a spectrum, formation prooxidation stress and dysfunction endothelium. Crucial importance in it plays a degree of weight of an anemia, so expressiveness hypoxia. It is shown, that metabolic to disorganization in conditions of decrease vasodilatum function endothelium, it may be accompanied by occurrence of clinical attributes development ischemic illness of heart.